2020
DOI: 10.2196/15149
|View full text |Cite
|
Sign up to set email alerts
|

Health Personnel’s Perceived Usefulness of Internet-Based Interventions for Parents of Children Younger Than 5 Years: Cross-Sectional Web-Based Survey Study

Abstract: Background Approximately 10%-15% of children struggle with different socioemotional and psychological difficulties in infancy and early childhood. Thus, health service providers should have access to mental health interventions that can reach more parents than traditional face-to-face interventions. However, despite increasing evidence on the efficacy of internet-based mental health interventions, the pace in transferring such interventions to health care has been slow. One of the major suggested b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
2
1
0
1
Order By: Relevance
“…Evidence indicates that women in the perinatal period who do not understand the local language or have a different cultural background may refrain from using internet-based interventions [ 54 , 55 ]. Moreover, 17 of our participants would not recommend internet-based interventions to patients with severe mental disorders, which concurs with the recommendations of the National Institute for Health and Care Excellence (NICE) guidelines [ 92 ] and with findings on the perceptions of health practitioners [ 75 ]. However, none of the interviewees suggested that women should be screened before recommending an internet-based intervention.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Evidence indicates that women in the perinatal period who do not understand the local language or have a different cultural background may refrain from using internet-based interventions [ 54 , 55 ]. Moreover, 17 of our participants would not recommend internet-based interventions to patients with severe mental disorders, which concurs with the recommendations of the National Institute for Health and Care Excellence (NICE) guidelines [ 92 ] and with findings on the perceptions of health practitioners [ 75 ]. However, none of the interviewees suggested that women should be screened before recommending an internet-based intervention.…”
Section: Discussionsupporting
confidence: 84%
“…According to our findings, 25 interviewees have a positive perception of internet-based interventions, believing them to be effective and suitable for use by affected persons. This corresponds to previous studies examining health professionals’ perceptions of internet-based interventions for the postpartum period [ 59 ] and for parents of young children with mental health problems [ 75 ]. By contrast, with respect to online psychotherapeutic interventions for diagnosed depression, Montero-Marin and colleagues suggested that primary health care personnel might show resistance to patients’ use of internet-based interventions [ 76 ].…”
Section: Discussionsupporting
confidence: 82%
“…Digital interventions can provide standardized, evidence-based and accessible care ‘where parents are’, that is, in their local communities, at home, and online. Parents actively search for information about infant sleep and health online [ 7 , 8 ], and most parents and HPs are interested in internet-based infant sleep programs [ 8 , 9 ]. Despite this, research on internet- and mobile-based interventions (IMIs) for pediatric insomnia in typically developed young children is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos anos, pais de bebês e crianças que nasceram prematuros costumam consultar a internet, antes mesmo de um profissional de saúde, por meio de mecanismos de busca e/ou redes sociais para obter informações relacionadas à saúde e aos cuidados com seus filhos (Størksen et al, 2020). Mais especificamente, pais de bebês que permaneceram na UTIN buscam plataformas responsivas, cursos de educação à distância (EaD) e aplicativos móveis, a partir de seus telefones celulares, para pesquisar mais informações sobre a saúde e o bem-estar de seus bebês (Orr et al, 2017).…”
Section: Introductionunclassified